2020
DOI: 10.3389/fmolb.2020.573327
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Multi-Organ miRNA-mRNA Regulatory Network in LPS-Mediated Endotoxemic Mice: Exploring the Shared Underlying Key Genes and Mechanisms

Abstract: BackgroundTo this day, the molecular mechanism of endotoxin-induced multi-organ failure has not been completely clarified. This study aimed to construct an miRNA-mRNA regulatory network and identify main pathways and key genes in multi-organ of LPS-mediated endotoxemic mice.MethodsPublic datasets from six mRNA and three miRNA microarray datasets were downloaded from the GEO website to screen final differentially expressed genes (FDEGs) and hub genes in the heart, lung, liver, and kidney of LPS-mediated endotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…However, in our study, the CCL2 mRNA level did not significantly decline after Nlrp3 knockout, which was probably related to the large individual differences in the WT + LPS group. Another bioinformatics study showed that CXCL9 is one of the key genes involved in multiple organ injuries caused by LPS in mice [ 31 ]. While the renal interstitial infiltration was relatively mild due to the low dose of LPS, the results of inflammatory factors suggest that Nlrp3 deletion attenuated renal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, the CCL2 mRNA level did not significantly decline after Nlrp3 knockout, which was probably related to the large individual differences in the WT + LPS group. Another bioinformatics study showed that CXCL9 is one of the key genes involved in multiple organ injuries caused by LPS in mice [ 31 ]. While the renal interstitial infiltration was relatively mild due to the low dose of LPS, the results of inflammatory factors suggest that Nlrp3 deletion attenuated renal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…A small increase in expression of CCR1, CCR2, and CCR6 persisted at 24 h. Given their respective roles in the mediation of PAMP response, a sustained elevation with MSM may reflect a beneficial response that allows for a more efficient immune response to additional DAMP signals. CXCL9 is a chemokine that is associated with skeletal muscle damage [34] and confers anti-microbial activity in the presence of IFN-gamma [35]. CFH (Factor H) down-regulates neutrophils and monocytes via a complement pathway [36] and may have anti-inflammatory activity [37].…”
Section: Discussionmentioning
confidence: 99%
“…In in vitro experiments, miR-340-5p mimic pretreatment can alleviate the oxidative stress injury induced by LPS, suggesting that miR-340-5p can protect myocardial function by reducing the level of myocardial oxidative stress. In our previous bioinformatics analysis, we demonstrated that MyD88 may be the hub gene of SIC [ 23 ], and the predictive analytics showed that MyD88 is the target gene of miR-340-5p. In order to further investigate whether miR-340-5p affects the level of myocardial oxidative stress by regulating MyD88 in SIC, we confirmed the interaction of miR-340-5p with MyD88 via the dual-luciferase reporter assay and RNA pull-down assay.…”
Section: Discussionmentioning
confidence: 99%
“…The animals were divided into four groups: the control group, LPS group, miR-340-5p group, and miR-340-5p-combined LPS group. As previously described, mice were intraperitoneally injected with LPS (Sigma-Aldrich, 10 mg/kg) for 6 hours to establish the sepsis-induced cardiomyopathy model [ 23 ]. In the control group (OE-NC group), the mice were intramyocardial injected with 20 μ l (1 × 10 11 vg/mice) of Adenoassociated Virus- (AAV-) 9 negative control (Shanghai GeneChem Co., Ltd., China) at day 0 and were intraperitoneally injected with phosphate-buffered saline (PBS) buffer for 6 hours at day 21.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation